Early Childhood Stimulation in Tanzania : Findings from a Pilot Study in Katavi Region - World Bank Group (World Bank, Washington, DC, 2018)
This study qualitatively explores early stimulation practices in Katavi region, Tanzania. It also quantitatively investigates the links between these early stimulation practices and development of children 0-3 years of age in the Katavi region. A comparative qualitative case study was carried out in Zanzibar region and findings have been presented throughout discussion section of this report, in parallel to the case of Katavi. Through this work the research team has developed a robust package of early childhood development research tools that have been carefully adapted and tested for use in Tanzania. The study uses and validates the combined use of tools to measure children's development (the CREDI tool) and the home environment (the HOME tool) for the first time in Tanzania. This package includes a complete survey including culturally-adapted, Kiswahili versions of the CREDI and HOME tools plus a caregiver information form that have all been digitized for data collection using electronic tablets. There is an accompanying video that guides users through the digitized version of the tool. The package also includes a four-day training guide with power points that may be used to prepare enumerators to collect the survey data. The adapted versions of these tools are free to users and easily accessible for others who wish to explore early stimulation and child development in Tanzania.